Vacuolar Membrane ATPase Activity 21 Predicts a Favorable Outcome and Acts as a Suppressor in Colorectal Cancer - Zhang, Fan; Shen, Hao; Fu, Yating; Yu, Guanyu; Cao, Fuao; Chang, Wenjun; Xie, Zhongdong (Frontiers in Oncology, 2021)
Extracellular and/or intracellular manipulation of pH in tumor may have noticeable potential in cancer treatment. Although the assembly factor genes of V0 domain of V-ATPase complex are required for intracellular pH homeostasis, the significance of them is largely unknown in colorectal cancer (CRC). Bioinformatics was used to identify the candidates from known assembly factor genes of V0 domain, which were further evaluated by immunohistochemistry (IHC) in CRC and adjacent normal specimens from 661 patients. Univariate and multivariate Cox analysis were adopted to evaluate factors contributing to prognosis. The effects of expression variations of VMA21 on tumor growth were assessed with in vitro and in vivo models. Of 5 known assembly factors, only VMA21 was identified as the differently expression gene between CRC and adjacent normal tissues at both mRNA and protein levels. High-VMA21 patients had higher differentiation grade and longer disease-specific survival (DSS) at stage I-III disease. Tumor with high VMA21 is also an independent predictor (Hazard ratio, 0.345; 95% confidence interval, 0.123-0.976) for DSS with the covariates including TNM stage and differentiation grade. We observed that VMA21 overexpression reduced the growth of CRC and its knockdown increased the tumor growth by using in vitro and/or in vivo CRC model. High VMA21 expression suppresses CRC growth and predicts a favorable DSS at stage I-III disease.